Your explanation of the numerical equivalent of \( 12^{-5} \cdot 12^{7} \) is correct! Here’s a concise breakdown of the steps:
-
Product Rule of Exponents: When you multiply expressions with the same base, you add the exponents. \[ 12^{-5} \cdot 12^{7} = 12^{-5 + 7} \]
-
Simplify the Exponents: \[ -5 + 7 = 2 \] So, \[ 12^{-5 + 7} = 12^{2} \]
-
Calculate \( 12^2 \): \[ 12^2 = 12 \cdot 12 = 144 \]
In conclusion, the numerical equivalent of \( 12^{-5} \cdot 12^{7} \) is indeed \( 144 \). Great job summarizing the process!